Implementation of Environtmentally Friendly Exhibition Booths by PT. City Neonindo Indah Murni: - Sa'diyah, Halimatus (Politeknik Pariwisata NHI Bandung, 2024)
In contemporary society, the imperative to reduce carbon footprints and mitigate other environmental impacts has become increasingly paramount. Businesses and industries are under mounting pressure to innovate and incorporate environmentally friendly practices across all sectors, including those historically perceived as less eco-friendly, such as exhibition stands. This research examines the perspective of PT City Neonindo Indah Murni, a leading exhibition stand contractor, regarding environmentally conscious exhibition stand design. The primary focus of this study is to investigate the utilization of environmentally friendly materials in exhibition stand construction. It is anticipated that the research findings will make a significant contribution to the general development of environmentally sustainable exhibition stands, which can be widely applied in exhibitions and by other stand contractors. The research methodology employs a qualitative descriptive approach. Data collection processes involve interviews, observations, documentation studies, and literature reviews. As a final step, the data analysis process will utilize an interactive model approach, subsequently validated through source triangulation to verify the validity of the research conclusions. Based on the data collection steps undertaken, it can be posited that PT City Neonindo Indah Murni, as one of Indonesia's preeminent stand contractors, has demonstrated efforts to utilize more environmentally friendly materials and implement reuse concepts for certain components. However, there remains scope for improvement through further research into the exploration of alternative materials such as bamboo, recycled fiberboard, or other eco-friendly composite materials, as well as the development of more efficient and environmentally friendly modular construction methods.